2022
DOI: 10.3389/fmicb.2022.819086
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Functional Characterization of the Polyketide Synthases Based on Genome Mining of Preussia isomera XL-1326

Abstract: Fungal polyketides (PKs) are one of the largest families of structurally diverse bioactive natural products biosynthesized by multidomain megasynthases, in which thioesterase (TE) domains act as nonequivalent decision gates determining both the shape and the yield of the polyketide intermediate. The endophytic fungus Preussia isomera XL-1326 was discovered to have an excellent capacity for secreting diverse bioactive PKs, i.e., the hot enantiomers (±)-preuisolactone A with antibacterial activity, the single-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…With the development of bioinformatics and the applying next-generation sequencing data, there has indeed been more focus on natural product discovery based on genomics (Garima et al, 2022b ; Luo et al, 2022 ). Genome mining has become a powerful tool to discover compounds, identify cryptic biosynthetic gene clusters, characterize the potential biosynthetic pathways, and predict the skeletal structure of the relative products (Liu Q. et al, 2022 ; Liu T. et al, 2022 ; Kalra et al, 2023 ). An increasing understanding of high-quality genome sequencing and genome mining techniques coupled with the introduction of powerful computational toolkits facilitates the process of connecting these gene clusters with key compounds (Li et al, 2016 ).…”
Section: Strategy To Discover Lichen Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of bioinformatics and the applying next-generation sequencing data, there has indeed been more focus on natural product discovery based on genomics (Garima et al, 2022b ; Luo et al, 2022 ). Genome mining has become a powerful tool to discover compounds, identify cryptic biosynthetic gene clusters, characterize the potential biosynthetic pathways, and predict the skeletal structure of the relative products (Liu Q. et al, 2022 ; Liu T. et al, 2022 ; Kalra et al, 2023 ). An increasing understanding of high-quality genome sequencing and genome mining techniques coupled with the introduction of powerful computational toolkits facilitates the process of connecting these gene clusters with key compounds (Li et al, 2016 ).…”
Section: Strategy To Discover Lichen Natural Productsmentioning
confidence: 99%
“…With the help of gene knockout studies, it has been observed that cryptic PKS gene codes for PKS required for the biosynthesis of the representative polyketide orsellinic acid. Polyketides synthesized by three types of multidomain polyketide synthases in the sequential acyl acetyl-polymalonyl pathway are major, structurally diverse classes of natural products (Lin and Qu, 2022 ; Liu Q. et al, 2022 ). In the case of bacteria and fungi, PKSs belong to types I and II, while type III is present in higher plants.…”
Section: Strategy To Discover Lichen Natural Productsmentioning
confidence: 99%
“…Alternatively, such linkages result from nrPKS‐catalyzed transformations of nascent, acyl carrier protein‐bound intermediates [7, 8] . Among the ester‐linked OA dimers, lecanoric acid ( 2 ), a lichen metabolite also produced by filamentous fungi, displays various biological activities, including histidine decarboxylase inhibitory, [9] radical scavenging, [10, 11] and antifungal activities [12] . Three nrPKSs from different fungi have been shown to yield the didepside 2 , all without the involvement of post‐PKS tailoring enzymes.…”
Section: Figurementioning
confidence: 99%
“…[12] Three nrPKSs from different fungi have been shown to yield the didepside 2, all without the involvement of post-PKS tailoring enzymes. These nrPKSs (AN7909 from Aspergillus nidulans, [7,8] CPUR_07425 from Claviceps purpurea, [13] and Preu6 from Preussia isomera, [12] ) share the same domain architecture, that is, SAT (starter acyl transferase)-KS (ketoacyl synthase)-AT (acyl transferase)-PT (product template)-ACP1 and 2 (acyl carrier protein 1 and 2)-TE (thioesterase) (Figure S1, Table S1). When expressed in Saccharomyces cerevisiae, AN7909 affords the diaryl ether diorcinolic acid (3) with only trace amounts of 2.…”
mentioning
confidence: 99%
“…Thus, apparently closely related nrPKSs and their similar TE domains may facilitate different chemistries.Recently, we identified the nrPKS Preu6 from the endophytic fungus Preussia isomera XL-1326. [12] Upon heterologous expression in S. cerevisiae BJ5464-NpgA, Preu6 affords 2 efficiently (isolated yield: 162.2 mg L À 1 , [12] ) with little OA released (Figure 2A). Surprisingly, although the Preu6 domain architecture is identical to those of AN7909 and CPUR_07425, the SAT and TE domains of Preu6 share only low similarity with those of the other two…”
mentioning
confidence: 99%